Severe Aplastic Anemia as First Manifestation of Classical Hodgkin Lymphoma - Pedrosa, Cláudia L. (Case Rep Hematol, 2021)
Autoimmune cytopenia, a known paraneoplastic complication of lymphoid neoplasms, may occur before, concurrently, at relapse, or even years after completion of lymphoma treatment. In the case of Hodgkin lymphoma (HL), it is thought that immune dysregulation, typical of this neoplasm, may be involved in the genesis of these manifestations. We report a 57-year-old male presenting with stage IIIA, International Prognostic Score (IPS) 4, nodular sclerosis HL, and severe AA (SAA) confirmed on the histologic exam of the bone marrow that showed severe marrow hypoplasia due to a decrease in the elements of the three cell linages with left shift of the myeloid maturation. Immunosuppression with steroids and cyclosporine A was started. Eltrombopag and G-CSF were also added. In spite of prompt initiation of immunosuppressive therapy, the patient presented an unfavorable outcome with progressive pancytopenia and severe acute cerebral hemorrhagic event. The patient died 59 days after admission. Although autoimmune disorders are described in HL, its concomitant diagnosis is extremely rare. Our case shows a rare instance of SAA as the first manifestation of HL.